The Potential of Pancreatic Organoids for Diabetes Research and Therapy - Bittenglova, Katerina; Habart, David; Saudek, Frantisek; Koblas, Tomas (Islets, 2021)
The success of clinical transplantation of pancreas or isolated pancreatic islets supports the concept of cell-based cure for diabetes. One limitation is the shortage of cadaver human pancreata. The demand-supply gap could potentially be bridged by harnessing the self-renewal capacity of stem cells. Pluripotent stem cells and adult pancreatic stem cells have been explored as possible cell sources. Recently, a system for long-term culture of proposed adult pancreatic stem cells in a form of organoids was developed. Generated organoids partially mimic the architecture and cell-type composition of pancreatic tissue. Here, we review the attempts over the past decade, to utilize the organoid cell culture principles in order to identify, expand, and differentiate the adult pancreatic stem cells from different compartments of mouse and human pancreata. The development of the culture conditions, effects of specific growth factors and small molecules is discussed. The potential utility of the adult pancreatic stem cells is considered in the context of other cell sources.
Keywords: buněčná diferenciace; stem cell therapy; Humans; Pluripotent Stem Cells; pluripotentní kmenové buňky; transplantation; ALDH; pancreas; CD133; lidé; adult stem cells; PROCR; pankreas; Diabetes Mellitus; Pancreas; beta cell; LGR5; Cell Differentiation; Organoids; organoidy; diabetes; progenitor cells; beta cell regeneration; diabetes mellitus